2009
DOI: 10.1038/sj.bjc.6605112
|View full text |Cite
|
Sign up to set email alerts
|

Modest effect of p53, EGFR and HER-2/neu on prognosis in epithelial ovarian cancer: a meta-analysis

Abstract: BACKGROUND: P53, EGFR and HER-2/neu are the most frequently studied molecular biological parameters in epithelial ovarian cancer, but their prognostic impact is still unequivocal. We performed a meta-analysis to more precisely estimate their prognostic significance. METHODS: Published studies that investigated the association between p53, EGFR and HER-2/neu status and survival were identified. Meta-analysis was performed using a DerSimonian -Laird model. Publication bias was investigated using funnel plots an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 106 publications
(87 reference statements)
3
75
2
Order By: Relevance
“…The expression rates of EGFR in ovarian cancer vary due to different evaluation techniques (gene amplification or protein overexpression by IHC) and reported as 4-70% in the literature (de Graeff et al, 2009). In our study, membranous EGFR positivity was observed in 45.1% of the study group, which was compatible with the results of a previous study performed by Noske et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…The expression rates of EGFR in ovarian cancer vary due to different evaluation techniques (gene amplification or protein overexpression by IHC) and reported as 4-70% in the literature (de Graeff et al, 2009). In our study, membranous EGFR positivity was observed in 45.1% of the study group, which was compatible with the results of a previous study performed by Noske et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Study quality was assessed independently by two authors (Haiyan Chen and Yeting Hu) according to our modified criteria (Table S1). These criteria were developed to assess the quality of included studies, based on the representativeness of cases and controls, ascertainment of CRC, characteristics of control, sample size and genotyping examination (Thakkinstian et al 2005;Gao et al 2011;De Graeff et al 2009). The total scores ranged from 0 to 10, with higher scores indicating better quality.…”
Section: Data Extraction and Assessment Of Study Qualitymentioning
confidence: 99%
“…A meta-analysis of 62 studies addressing the prognostic significance of p53 abnormalities using IHC or mutational analysis found that overall p53 aberrant status confers poor survival, but the effect was modest (de Graeff et al 2009). …”
Section: Ovarian Cancermentioning
confidence: 99%